Adrenalitis associated with Leishmania infantum infection in a maned wolf (Chrysocyon brachyurus) - Carvalho, Tatiane F.; Neves, Gabriela G.; Gomes, Priscilla P. R.; Tinoco, Herlandes P.; Pessanha, Angela T.; Malta, Marcelo C. C.; Soave, Semíramis A.; Medeiros, Lilian B.; Mol, Juliana P. S.; Fujiwara, Ricardo T.; Paixão, Tatiane A.; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2015)
This report describes a case of visceral leishmaniasis characterized by adrenalitis with intralesional Leishmania sp. amastigotes in a 16 year-old maned wolf (Chrysocyon brachyurus). The animal had been previously diagnosed as infected with Leishmania infantum by serology and xenodiagnosis. The only organ in which amastigotes were detected by histopathology and immunohistochemistry was the adrenal gland, which presented multifocal infiltration of lymphocytes, plasma cells and macrophages containing intracytoplasmic amastigotes. The animal had no other lesions of visceral leishmaniasis, except for renal and splenic amyloidosis and pancreatitis that may be associated with the disease. Importantly, the maned wolf had an intratubular seminoma in the testis, which to the best of our knowledge is the first reported case of testicular tumor in this species.